PENGARUH METODE EDUTAINMENT TERHADAP KEMAMPUAN BERHITUNG PERMULAAN SISWA KELAS I SD - Prasmita, Dyah Sari; Kesumawati, Nila; Dedy, Adrianus (Jurnal Pendidikan Dasar Flobamorata, 2024)
The aim of this study was to determine the effect of the edutainment method on the numeracy skills of first grade students at SD Negeri 07 Buay Pemaca. The method used is an experimental method with a pre-experimental research design and a one grub pretest posttest design type. The population taken is all first grade students, totaling 28 students. The sample taken was class 1 which totaled 28 students as the class that would be tried using the edutainment method. In taking samples using total sampling technique. The data collection technique used in this study is a test used for the ability to calculate the beginning. The data analysis technique used the Paired Sample T-Test. The conclusion from the results of this study is that there is an effect of the edutainment method on the initial numeracy skills of grade 1 students at SD Negeri 07 Buay Pemaca.